The revision and phylogenetic position of Hippasa bifasciata Buchar, 1997 (Araneae, Lycosidae) - Changjun Wu; Zehong Tao; Yang Wang; Yufa Luo (Biodiversity Data Journal)
Hogna Simon, 1885 is the second-largest genus in the family Lycosidae after Pardosa C. L. Koch, 1847 (517 species), including 232 species so far. This genus has a cosmopolitan distribution spanning multiple continents. However, only four species (Hogna rubetra (Schenkel, 1963), Hogna trunca Yin, Bao & Zhang, 1996, Hogna jiafui Peng, Yin, Zhang & Kim, 1997 and Hogna arborea Lo, Wei & Cheng, 2023) have been recorded in China.A new combination, Hogna bifasciata (Buchar, 1997), comb. nov. (from Yunnan and Sichuan Provinces in south-western China), is proposed with both morphological and molecular evidence. Detailed morphological descriptions, photographs, scanning electron micrographs and a distribution map are provided. This species is distinguished from congeners by the unique structure of the female epigyne and its somatic pattern. Molecular phylogenetic analyses suggest H. bifasciata (Buchar, 1997) and all analysed Hogna species cluster together within the subfamily Lycosinae and the species is sister to the group, including Hogna frondicola Emerton, 1885, Hogna carolinensis Walckenaer, 1805 and Hogna crispipes L. Koch, 1877.